Poverty and malaria morbidity in the Jirapa District of Ghana: A count regression approach - Paul Kwame Nkegbe; Naasegnibe Kuunibe; Samuel Sekyi (Cogent Economics & Finance, 2017)
Malaria potentially affects everyone in the tropics and sub-tropics, however, the poor and vulnerable are worse affected mainly due to the socio-economic constraints that confront them. In Ghana, the Upper West Region, which is the poorest, is one of the worse affected in terms of malaria burden. Given social and economic factors directly relate to malaria morbidity, global malaria control strategy unfortunately has not particularly targeted the effects of socio-economic deprivation on the disease morbidity and control. This study investigates the linkages between poverty and malaria morbidity using count data models, with Jirapa District in the Upper West Region of Ghana as the study area. Empirical results confirm the presence of poverty in the study area as more than half of households depend on heads whose incomes are below the poverty line of US1 per day and that significant relationships exist between poverty and education on the one hand and malaria morbidity on the other, since gender and level of education of household head, and household poverty situation are significant determinants of malaria morbidity. The study thus recommends that policies aimed at reducing and/or eradicating malaria should include measures to increase income earning capacity of households in the study area.
Keywords: I14; I15; I30; 330; malaria; morbidity; underdispersion; generalized Poisson model; Ghana